A novel fixing method for Mg-based specimens used in the in-vitro immersion test. Issue 4 (5th June 2017) - Tan, Cui; Zhou, Juncen; Li, Qing
Abstract : Purpose: The aim of this paper is to predict the in-vivo degradation behaviour of Mg-based implants through in-vitro immersion test. Design/methodology/approach: A novel placement mode arming to mimic the in-vivo situation was investigated in this work. Specimens were mounted on bones and then immersed in dynamic Hank's solution. Findings: The degradation behaviour of the specimen's two sides is unequal. The bottom side which clings to the bone was isolated from solution in the early stage. During the late immersion period, there was crevice corrosion appearing on the bottom side. Weight loss and mechanical properties of specimens were also affected by the placement mode. Research limitations/implications: Placement mode reported here have guiding significance for degradation behaviour of bio-implants in the clinical study. Social implications: Placement mode reported here have guiding significance for degradation behaviour of bio-implants in the clinical study. Originality/value: A novel placement mode arming to mimic the in-vivo situation was investigated in this work, which was better fit the actual in vivo immersion situation.